ASSAY OF ACETYLSALICYLIC ACID IN DRUG PRODUCTS BY DIFFERENTIAL SCANNING CALORIMETRY - A. M. Stoinova; A. V. Ponomareova; Ya. M. Stanishevskiy (Разработка и регистрация лекарственных средств, 2019)
Five dosage forms from various manufacturers containing acetyl salicylic acid was investigated with the DSC method. It was found that the amount of acetylsalicylic acid in these preparations is equal to 80-85 wt.%, which corresponds to the regulatory framework of the SP XIII.